2011
DOI: 10.1002/pen.22040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long chain branching on nonisothermal crystallization behavior of polyethylenes synthesized with constrained geometry catalyst

Abstract: Nonisothermal crystallization behavior of linear and long chain branched (LCB) polyethylene (PE) samples having similar molecular weight but different long‐chain branching densities (LCBD) up to 0.44 C per 1000 carbons was investigated using differential scanning calorimetry (DSC) at various scanning rates. The LCB PE samples were prepared in our high‐temperature, high‐pressure continuous stirred‐tank reactor (CSTR) system using the constrained geometry catalyst. The existence of LCB was found to affect the PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 65 publications
4
21
0
Order By: Relevance
“…In particular, the approach suggested by Vyazovkin has been successfully applied in the determination of Δ E χ. According to this technique Lntrue(dχdttrue)χ=CteΔEχRTχ where ( dχ/dt ) χ and T χ are the rate of crystallization and the temperature at a given level of crystallization χ, respectively. The activation energy of crystallization can be obtained from the slope of the plot of ln( dχ/dt ) χ as a function of 1/ T χ .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In particular, the approach suggested by Vyazovkin has been successfully applied in the determination of Δ E χ. According to this technique Lntrue(dχdttrue)χ=CteΔEχRTχ where ( dχ/dt ) χ and T χ are the rate of crystallization and the temperature at a given level of crystallization χ, respectively. The activation energy of crystallization can be obtained from the slope of the plot of ln( dχ/dt ) χ as a function of 1/ T χ .…”
Section: Resultsmentioning
confidence: 91%
“…A parameter that may be calculated from the crystallization curves is the activation energy of crystallization, Δ E χ . Several methods have been proposed in the literature for estimating thermal activation energies . In particular, the approach suggested by Vyazovkin has been successfully applied in the determination of Δ E χ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[73] Recently, however, Wang and co-workers [183] found that LCB had considerable effects on the nonisothermal crystallization of PE samples in the DSC study of long-chain branched PEs (LCBD up to 0.44C/1000 Cs) prepared by CSTR technique with CGC-Ti catalyst. [9] The crystallization enthalpy and the ultimate crystalline degree decreased with increasing LCBD.…”
Section: Differential Scanning Calorimeter (Dsc)mentioning
confidence: 99%
“…As we can see that the value of t 1/2 was reduced with increasing cooling rate. The curve was fitted with power model of non‐linear regression, it can be empirically as : t1/2=aϕb …”
Section: Resultsmentioning
confidence: 99%